Yield-limiting plant nutrients for maize production in northwest Ethiopia. (7th February 2022) - Amare, Tadele; Alemu, Erkihun; Bazie, Zerfu; Woubet, Asmare; Kidanu, Selamyihun; Alemayehu, Beamlaku; Awoke, Abrham; Derebe, Assefa; Feyisa, Tesfaye; Tamene, Lulseged; Kerebh, Bitewlgn; Wale, Sefinew; et al.
Summary: The potential yield of improved maize varieties usually cannot be fully realised mainly due to inappropriate soil nutrient management practices in most parts of Ethiopia. Site-specific fertiliser recommendations are rarely used in the farming systems of Ethiopia. There is also a lack of data to develop or validate decision support tools for targeting specific crop production. A study was conducted for three consecutive rainy seasons (2016–2018) in the maize belt of the north-western parts of the Amhara National Regional State of Ethiopia. The objectives were to obtain the maximum achievable yield potential of maize, determine the most yield-limiting nutrients and create a database of maize responses to applied nutrients so that decision support tools could be developed for the study areas. Treatments were individual nutrients (nitrogen (N), phosphorus (P) and potassium (K)) and combinations of the three. In some treatments, NPK was also combined with sulphur, zinc, lime and compost. Two hybrid maize varieties (BH-540 and BH-660) adaptable to the study areas were used. BH-540 was used for the Mecha district, while BH-660 was used for the south Achefer, Jabitahnan–Burrie–Womberma districts. Maize yield increased by more than 50% due to fertiliser applications compared to without fertiliser. The study showed that the possibility of increasing maize productivity to more than 12 t ha -1 for the study sites. The most yield-limiting nutrient in the study sites was N, followed by P; K was not a yield limiting. Without N the yield of both varieties was non-significant from the control (without added nutrients). Maize grain yield did not respond to application of lime, compost, zinc and sulphur. The result also showed very high variability across sites, indicating that it is important for policymakers, farmers and investors to consider site-specific fertiliser recommendations. Finally, a database containing intensive plant response to NPK for maize was generated and could be used as input in site-specific decision support tools development.